Conclave - Harris, Robert, 1957- (Alfred A. Knopf, 2016)
The Pope is dead. Behind locked doors of the Sistine chapel, 118 cardinals from around the world will cast their votes in the world's most secretive election. They are holy men, but they are men of the world, and they have rivals. And over the next seventy-two hours one of them will become the most powerful spiritual figure on earth.